Bytes and Rhythms – Delving into the Tech-Driven Evolution of Food and Music - Covaci, Alexandra (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2023: Proceedings of the 29th Brazilian Symposium on Multimedia and the Web, 2023)
In the rapidly advancing domain of design and technology, the transition from a predominantly human-centred approach to a more encompassing more-than-human perspective is gaining traction. This paper investigates the implications of such a shift, focusing on the domains of music creation and culinary experiences—two intrinsic human activities deeply embedded within larger ecosystems. Utilising immersive Virtual Reality (VR) methodologies, we examine the intricate relationship musicians have with their sonic environments and the profound connections diners establish with the food life-cycle. Our research highlights the constraints of an approach that prioritises only human experiences, unveiling potential avenues for more holistic, interconnected engagements. By incorporating more-than-human elements, from the ambient subtleties influencing musical performances to the comprehensive journey of food from origin to consumption, we advocate for a design perspective that is both holistic and integrative. This perspective not only enriches human experiences but also promotes a balanced coexistence with the entities that influence our daily interactions.